2020
DOI: 10.1038/s41467-020-18128-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac dopamine D1 receptor triggers ventricular arrhythmia in chronic heart failure

Abstract: Pathophysiological roles of cardiac dopamine system remain unknown. Here, we show the role of dopamine D1 receptor (D1R)-expressing cardiomyocytes (CMs) in triggering heart failure-associated ventricular arrhythmia. Comprehensive single-cell resolution analysis identifies the presence of D1R-expressing CMs in both heart failure model mice and in heart failure patients with sustained ventricular tachycardia. Overexpression of D1R in CMs disturbs normal calcium handling while CM-specific deletion of D1R ameliora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 45 publications
0
41
0
1
Order By: Relevance
“…Western blotting was performed as previously described 53 . Tissues and cells were homogenized in ice-cold RIPA buffer containing protease inhibitor (cOmplete Protease Inhibitor Cocktail, Merck) and phosphatase inhibitor (PhosSTOP, Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as previously described 53 . Tissues and cells were homogenized in ice-cold RIPA buffer containing protease inhibitor (cOmplete Protease Inhibitor Cocktail, Merck) and phosphatase inhibitor (PhosSTOP, Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…DA receptors are expressed in the heart ( 39 , 40 ), but the source of DA is not clear. One possible hypothesis is that sympathetic noradrenergic neurons release DA.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, evidence has shown that dysfunction in the D3R signaling system is associated with an increase in blood pressure in mice ( 14 , 15 ). Emerging evidence suggests the existence of an intracardiac dopaminergic system plays a role in regulating cardiac function, mainly mediated by the dopamine receptor subtypes D1 and D3 ( 16 , 17 ). In particular, the global loss of D3R function has been shown to negatively impact cardiac function and exacerbate the progression of fibrosis in mice ( 16 ).…”
Section: Introductionmentioning
confidence: 99%